A Low-cost, Safe, and Effective Method for Smoke Evacuation in Laparoscopic Surgery for Suspected Coronavirus Patients. Issue 1 (July 2020) - Mintz, Yoav; Arezzo, Alberto; Boni, Luigi; Chand, Manish; Brodie, Ronit; Fingerhut, Abe
Abstract : Supplemental Digital Content is available in the text